On functional identities involving n-derivations in rings - Vaishali Varshney; Shakir Ali; Naira Noor Rafiquee; Kok Wong (Journal of Mahani Mathematical Research)
In this paper, we explore various properties associated with the traces of permuting $n$-derivations satisfying certain functional identities that operate on a Lie ideal within prime and semiprime rings. Additionally, we address and discusscorrelated findings pertaining to left $n$-multipliers. Lastly, we enrich our results with examples that show the necessity of their assumptions.